Process Modelling of Isoamyl Acetate Synthesis Catalysed by Lipase from Candida antarctica in a Solvent-free System - Leong , Sim Siong; Azudin, Nurhazwani Yusoff; Shukor, Syamsul Rizal Abd (Taylor's University, 2014)
The objective of this work is to propose a reaction mechanism and develop a model for the synthesis of isoamyl acetate from isoamyl alcohol and acetate anhydride by using lipase from Candida antarctica in a solvent-free system. Ping-Pong Bi-Bi reaction mechanism with acetic anhydride and acetic acid inhibition is found to be the mechanism which is able to describe this reaction. Unknown parameters of the model developed are obtained by minimising deviation of model prediction from experimental result and it is performed by the Solver Tool in Microsoft Excel. The model prediction is found to match the experimental data quite well (average percentage error = 8.08%)